Reply to comment on ‘non-monotonic projection probabilities as a function of distinguishability’ - Gunnar Björk; Saroosh Shabbir (New Journal of Physics, 2014)
We reiterate that a non-monotonic behavior of projection probabilities can occur for most states irrespective of the number of particles involved, based solely on the choice of the projectors chosen for measurement. We further clarify that, contrary to the claim in the comment, our analysis is not intended to demonstrate quantum to classical transition. However, our results show that a non-monotonic behavior is not a necessarily a signature of such a transition.